(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The importance of promoting political through social media has become an important tool, as an increasing phenomenon, in the opinion industry, especially as a large percentage of voters own smart phones connected to the Internet, and thus facilitate the process of communication via social networking sites, which passes a huge amount of Given the importance of the subject at the present time, the present study focused on it and proceeded from a rupture problem formulated as follows: Is there an impact of political promotion through the social networking sites of the members of the People’s Assembly on the electoral participation of postgraduate students at Tishreen University . The study also aimed at the following: Determining the degree of interest of members of the People’s Assembly by means of social communication. Determining the degree of interaction of graduate students in the Faculty of Literature with the letters of political promotion to members of the People’s Assembly. Determining the impact of political promotion on the electoral participation of postgraduate students in the Faculty of Arts, Tishreen University. The researcher used the descriptive analytical approach, After the analysis, the study reached a number of results, the most important of which are the following: The lack of interest of members of the People’s Assembly Advertising through the means of social communication in a professional manner, which leads to the lack of interest in students of this propaganda due to lack of presence or attractiveness. And the lack of interest of members of the People’s Assembly means of social communication and communication skills with voters. And the lack of interest of graduate students in letters of political promotion through the means of social communication directed by members of the People’s Assembly. And the absence of an impact of messages to promote the political members of the People’s Assembly through the means of social communication on the electoral participation of postgraduate students, Tishreen University. ارتفعت أهمية الترويج السياسي عبر وسائل التواصل الاجتماعي، وأصبح من الأدوات الهامة، باعتباره ظاهرة يزداد تأثيرها، في صناعة الرأي ، خصوصاً وأن نسبة كبيرة من الناخبين يملكون الهواتف الذكية المرتبطة بشبكة الانترنت، وبالتالي تسهل عملية التواصل عبر مواقع التواصل الاجتماعي، التي تمرر كم هائل من المعلومات .ونظراً لأهمية الموضوع في الوقت الحالي قد ركزت الدراسة الحالية عليه وانطلقت من مشكلة رئيسية صيغت كالآتي: هل يوجد تأثير للترويج السياسي عبر مواقع التواصل الاجتماعي لأعضاء مجلس الشعب السوري على المشاركة الانتخابية لطلبة الدراسات العليا بجامعة تشرين؟ كما هدفت الدراسة إلى الآتي: تحديد درجة اهتمام اعضاء مجلس الشعب بوسائل التواصل الاجتماعي، وتحديد درجة تفاعل طلبة الدراسات العليا في كلية الآداب مع رسائل الترويج السياسي لأعضاء مجلس الشعب، بالإضافة إلى تحديد تأثير الترويج السياسي على المشاركة الانتخابية لطلبة الدراسات العليا في كلية الآداب بجامعة تشرين. وقد استخدمت الباحثة المنهج الوصفي التحليلي. وبعد التحليل توصلت الدراسة إلى مجموعة من النتائج من أهمها الآتي: عدم اهتمام أعضاء مجلس الشعب بالإعلان عبر وسائل التواصل الاجتماعي بشكل احترافي مما يؤدي إلى عدم اهتمام الطلبة بهذا الإعلان نتيجة عدم وجودها أو جاذبيتها، وعدم اهتمام أعضاء مجلس الشعب بوسائل التواصل الاجتماعي ومهارات التواصل مع الناخبين، وعدم اهتمام طلبة الدراسات العليا برسائل الترويج السياسي عبر وسائل التواصل الاجتماعي الموجهة من قبل أعضاء مجلس الشعب، وعدم وجود تأثير لرسائل الترويج السياسي لأعضاء مجلس الشعب عبر وسائل التواصل الاجتماعي على المشاركة الانتخابية لطلبة الدراسات العليا بكلية الآداب بجامعة تشرين.